2000
DOI: 10.1177/0533316400332006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Therapeutic Factors of Group Therapy in Schizophrenic Inpatients and Outpatients

Abstract: Although there is great interest and development in the investigation of group therapeutic factors, there are few studies regarding group psychotherapy with schizophrenic patients. Given the importance of both aspects in our work, the authors of this work have analyzed the therapeutic factors for schizophrenic patients in two types of group psychotherapy - inpatients and outpatients - based on Yalom's questionnaire of the therapeutic factors (altruism, cohesiveness, universality, interpersonal learning output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…From a clinical perspective, group psychotherapeutic treatments are also believed to offer social advantages relevant to this population [4,5,6,7,8], who often have smaller social networks and less satisfactory interpersonal relationships compared to a healthy population [9]. Seminal work on group therapeutic processes [10] (including group cohesion, instillation of hope, interpersonal learning and sharing of information) supports the notion that the group setting can be utilised as an agent of change in group psychotherapeutic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…From a clinical perspective, group psychotherapeutic treatments are also believed to offer social advantages relevant to this population [4,5,6,7,8], who often have smaller social networks and less satisfactory interpersonal relationships compared to a healthy population [9]. Seminal work on group therapeutic processes [10] (including group cohesion, instillation of hope, interpersonal learning and sharing of information) supports the notion that the group setting can be utilised as an agent of change in group psychotherapeutic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…However findings from the present study highlight that the Group Climate Questionnaire (MacKenzie, 1981) and the Group Climate Questionnaire-Short (MacKenzie, 1983) have relatively low scale development quality scores compared to other available tools. The discrepancy between the GCQ-S' low psychometric properties and high popularity might be because the GCQ-S is an extremely user-friendly tool, consisting of only 12 items and can be flexibly used by either a group member, group leader, or observer (DeChavez et al, 2000).…”
Section: Measuring Overall Group Processmentioning
confidence: 99%
“…Individuals suffering from chronic psychosis in the community often face significant social isolation (Reininghaus 2008). Group psychotherapy can offer these people a space to share personal experiences and an opportunity to mutually observe and reflect on emotions, thoughts and feelings (Kanas 1996;de Chavez 2000 (Maxmen 1973;Kanas 1986;Yalom 1983;de Chavez 2000). It has been suggested that, in a group, psychotic transference can be less intense because the patient has the opportunity to see the therapist as a real person and thus emotion can be dealt with and explored more safely (Gabrovsek 2009).…”
Section: Historymentioning
confidence: 99%
“…One perspective on group psychotherapy suggests that it works by stimulating empathy (Foulkes 1957;de Chavez 2000). The ability to show interest and empathy for others is not a spontaneous process in patients affected by schizophrenia (Haker 2009).…”
Section: The Difficulty Of Eliciting Emotional Response In Psychosismentioning
confidence: 99%